Learning & Teaching Statistical Methods in the Age of Modern Computing - Verma, Pashupati Nath (International Journal of Engineering and Management Research, 2025)
The evolution of data analytics and computational technologies has significantly transformed the landscape of statistical education and research. Traditional methods of data collection, manual computation, and interpretation are giving way to automated, real-time analytics powered by tools like R, Python, SPSS, Power BI, and machine learning algorithms. This paper examines the shifts across the data lifecycle—from collection and cleaning to analysis, visualization, and interpretation. It proposes strategic directions for academic curriculum development and guidelines for new researchers to remain relevant in the data-driven era. Emphasis is placed on a hybrid approach that combines foundational statistical knowledge with practical skills in data science and analytics. The integration of interdisciplinary methods, hands-on learning, ethical considerations, and real-world applications is highlighted as the future of statistical education and research.